Is a picture worth a thousand words? : Member checking using the sketchnoting approach - Kückmann, Marie-Ann [Verfasser] (My University, 2025)
“The question of validity is particularly important in the context of qualitative research. There have been numerous attempts to establish or reformulate criteria for validity and procedures for increasing validity. Member checking is one example. Although member checks are frequently integrated into qualitative studies, researchers do not always describe and explain them in detail in the corresponding reports. In this paper, I would like to contribute to the research on conducting member checks by presenting and discussing the approach of sketchnoting. I argue that there is potential (both in theory and practice) in using this means of communication: Relevant problems that might occur in the context of member checking are addressed, and the gap between transactional and transformational validity approaches is bridged. From the perspective of a process-oriented view of validity, a reflective process for participants and researchers is supported.” (author’s abstract; BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; 370; Berufsbildungsforschung; InnoVET; Validität; Qualitative Methode; Visualisierung